The effect on interest rate fluctuation towards Maybank’s profitability in Malaysia / Nur Farah Ismail and Nurhafizatul Shahira Zulkifli - Ismail, Nur Farah; Zulkifli, Nurhafizatul Shahira (Faculty of Business and Management, 2019)
This paper aim at finding out the effect on interest rate volatility towards Maybank’s profitability in Malaysia which the interest rates is monitor based on the base lending rate (BLR) that have been set by Maybank. The variables are considered are return on asset (ROA), return on equity (ROE), and net interest margin (NIM). This study required 28 years data which is equal to 116 data by quarterly for each variable from 1989 until 2017. Methodology used for this study is using Single Linear Regression with series data. Thereafter, econometric test is to be conducted to observe the relationship of the profitability with independent variables which is interest rate. Interactive software package E-view would be used for testing and analysing the data collected. This study is attempting to investigate there is a significant relationship between the independent variables with the ROA, ROE, and NIM, and which variables effect most to interest rate. Findings from previous study mostly show that interest rate volatility has a significant role in the determination of bank’s financial performance. As guidance to the past research that have been done, this study will examine the relationship between the bank’s profitability and interest rate.